2019
DOI: 10.1088/1755-1315/379/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

The study of Apple flour formulation for functional cookies

Abstract: The purpose of this study was to examine apple flour as a source of functional flour in various cookie formulas. Apple flour is applied as a substitute for flour in making cookies. The design used was a nested design [Nested Analisys], with two groups of apple varieties and three levels of formula adding apple flour which was nested in each variety, and repeated four times. Grouping is based on varieties, namely A = Anna and M = Manalagi, and the formula for adding apple flour to cookies is F0: 0%; F20: 20%, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Insoluble fiber was higher in A17 and A23 also due to differences between BWF and AF insoluble fiber content. Other authors studying apple-derived ingredients incorporation in baking products, also obtained an increase in fiber content [ 18 , 24 ]. The amount of fiber in GFB is an important aspect, both for its well-known health benefits, and also its particular influence in GF rheology dough behavior, as mentioned in Section 2.2 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Insoluble fiber was higher in A17 and A23 also due to differences between BWF and AF insoluble fiber content. Other authors studying apple-derived ingredients incorporation in baking products, also obtained an increase in fiber content [ 18 , 24 ]. The amount of fiber in GFB is an important aspect, both for its well-known health benefits, and also its particular influence in GF rheology dough behavior, as mentioned in Section 2.2 .…”
Section: Resultsmentioning
confidence: 95%
“…Thus, its incorporation in GFB, as expected, led to the raise of total phenols, ortho -diphenols and flavonoids content as well as antioxidant capacity. Other authors obtained also the increase of bioactive compounds and antioxidant capacity [ 15 , 17 , 20 , 23 , 24 ]. In particular, Mir et al [ 15 ] obtained much lower values, respectively, 0.82 mg GA g −1 and 0.063 mg Catechin g −1 for total phenols and flavonoids content, for its higher level of incorporation in crackers, nevertheless it was 9%, much lower than in the present work.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study; Zafar & Tusneem Kausar (2019) showed that sensory evaluation of cookies demonstrated that supplementation of guava flour improves all sensorial parameters. Ishartati et al (2019) indicated that the most preferred product by panelists is the level of substitution of Mamaliga apple flour 25% and 30%. Also, Al-Lami et al (2020) showed that sensory evaluation was best when mixed quinoa and rice by 50:50, which was characterized by acceptable characteristics.…”
Section: Sensory Characteristics Of Cookies With Oat and Unripe Banan...mentioning
confidence: 99%
“…Among the four varieties, Manalagi and Rome Beauty are more popular and available in the market [2]. In a study done by Ishartati et al [6], Manalagi and Anna apple flours were used to partially replace wheat flour in cookies formulation. The study suggested that the use of Manalagi apple flour resulted in cookies with higher fibre content compared to when Anna apple flour was used.…”
Section: Introductionmentioning
confidence: 99%